Factors associated with tuberculosis in persons deprived of liberty in Espírito Santo - Macedo, Laylla Ribeiro; Maciel, Ethel Leonor Noia; Struchiner, Claudio Jose (Revista de Saúde Pública, 2020)
OBJECTIVES: To calculate the rate of tuberculosis cases per prison unit in Espírito Santo; present the individual, clinical, and institutional characteristics of the cases in persons deprived of liberty (PPL); and analyze the association between these characteristics and treatment outcome in this population.METHODS: The study included cases of tuberculosis in the PPL of Espírito Santo from 2014 to 2016. Rate calculation, descriptive analysis and hierarchical logistic regression were performed considering the individual, clinical and institutional levels.RESULTS: The rate of diagnosed cases per prison unit in the state ranged from 0 to 17.3 cases per 1,000 inmates. Of all reported cases, 218 (72.6%) healed, 21 (7.0%) dropped out, 1 (0.3%) died of tuberculosis, 2 (0.7%) died from other causes, 56 (18.7%) transferred the treatment site and 2 (0.7%) developed drug-resistant tuberculosis. The adjusted analysis showed that supervised treatment ensures success (CR = 0.29; 95%CI 0.01–0.76).CONCLUSIONS: The study highlighted the importance of knowing the TB treatment outcome in the PPL to implement measures to reduce failure, and the contribution of supervised treatment in this process.